Expression of Concern: Novel fatty chain-modified GLP-1R G-protein biased agonist exerts prolonged anti-diabetic effects through targeting receptor binding sites. Issue 51 (22nd November 2022) - Wang, Maorong; Yao, Ping; Gao, Minpeng; Jin, Jian; Yu, Yerong
Abstract : Expression of Concern for 'Novel fatty chain-modified GLP-1R G-protein biased agonist exerts prolonged anti-diabetic effects through targeting receptor binding sites' by Maorong Wang et al., RSC Adv., 2020, 10, 8044–8053, ; https://doi.org/10.1039/C9RA10593J .